Inertial evaluation of the tyre-road interaction during emergency braking - Kashkanov, A.A.; Diorditsa, V.M.; Kucheruk, V.Yu.; Karabekova, D.Zh.; Khassenov, A.K.; Sharzadin, A.M. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
An improved method of evaluation of the parameters of braking efficiency in vehicles of M1 category has been proposed for expert examination of motor vehicle accidents. This method is based on the control of parameters which are able to significantly influence the friction processes in the contact tyre-road area. These parameters were discovered in the course of analysis of theoretical approaches to the evaluation of the quality of tyre-road interaction, analytical formulas used for evaluation of the main braking parameters (deceleration, stopping distance) as well as for experimental evaluation of parameters of inertia braking efficiency. The generalization of study results showed that existing expert methods of evaluation of the parameters of vehicle motion during emergency braking do not take into account the design of modern braking systems, tyres and psychological aspects of control of the braking process by a human operator. After processing experimental data, recommendations have been formed to improve the existing approaches and eliminate the discovered defects. The verification of the proposed recommendations allowed to establish the areas of their efficiency for M1 category vehicles on dry bituminous concrete and confirmed the need to conduct further studies for vehicles of other categories and other types and conditions of road surface within the framework of the developed general approach.
Шұғыл тежеу кезінде автокөлік дөңгелектерінің жолмен өзара əрекеттесуін инерциялық бағалау
Инерционная оценка взаимодействия автомобильных шин с дорогой при экстренном торможении
Keywords: friction forces; tyre; road surface; friction process; deceleration; stopping distance; expert examination of motor vehicle accidents